THE EFFECT OF USING BLOG ON THE TENTH GRADE STUDENTS' NARRATIVE WRITING QUALITY AT SMAN 1 PESANGGARAN IN THE 2022/2023 ACADEMIC YEAR - Widhya Putriana; Agus Wijaksono (Fakultas Keguruan dan Ilmu Pendidikan Universitas Bakti Indonesia, 2023)
The objective of this study was to investigate whether learners who study writing by using blog have better narrative writing quality than learners who do not. This study was quasi experimental study which employed X.4 as experimental group and X.5 as control group. The writer led this study in five meetings which was a meeting for pre-test, three meetings for teaching and learning activity, and a meeting for post-test. The data obtained from the results of writing tests and questionnaires. The use of independent sample t-test from using SPSS was used to analyze the data. Based on the outcome of data, there is a substantial effect of using blog on the 10th grade learners' narrative writing quality at SMAN 1 Pesanggaran in the 2022/2023 academic year. Furthermore, the mean score of both groups that is 85.3 for the experimental group and 76.5 for the control group respectively. In conclusion, the students who learned writing by using blog have better narrative writing quality than students who did not.